Heartstopper. Volume 2 - Oseman, Alice (Heartstopper, 2020)
"Nick and Charlie are best friends, but one kiss has changed everything. In the aftermath, Charlie is sure that Nick isn't interested, but Nick is more confused than ever. Love works in surprising ways, and Nick comes to see the world from a new perspective. He discovers all sorts of things about his friends, his family ... and himself."--Provided by publisher.